Pembinaan homeomorfisma dari sfera ke elipsoid. - Liau, Li Yun; Ahmad, Tahir (Department of Mathematics, Faculty of Science, 2003)
In this paper, we present the construction of homeomorphism from unit sphere; $S^2$ to ellipsoid which is one unit in xy-axis and its poles are at $z=2$ and $z=-2$; $E^2$ through Riemann surface structures. Proving techniques by construction and contradiction are highlighted.